Biomarkers of in vivo platelet activation in thoroughbreds during their first long-term training - Miglio, Arianna; Falcinelli, Emanuela; Mezzasoma, Anna Maria; Busechian, Sara; Rueca, Fabrizio; Gresele, Paolo; Antognoni, Maria Teresa (Frontiers in Veterinary Science, 2024)
Physical exercise has an activating effect on platelet function that differs between trained and untrained subjects, depending on the type of exercise and training status. In humans, soluble P-selectin (sP-sel) and platelet-derived extracellular vesicles (PEVs) are considered reliable markers of in vivo platelet activation during exercise. In untrained humans, they increase after transient physical exercise, whereas long-term training induces a decrease in their resting levels due to an improved ability to adapt to hemodynamic changes. The aim of this study was to assess whether circulating levels of sP-sel and PEVs may be useful markers to explore in vivo platelet function in never-trained Thoroughbreds during their first 4 months of incremental training. A total of 29 clinically healthy, untrained Thoroughbreds (17 males and 12 females) were enrolled. All horses were trained with the same training schedule (90 days). Blood samples were collected on the day the training program began (T0), 30 days (T30), and 90 days (T90) after its incremental increase to quantify platelet count, sP-sel (horse enzyme-linked immunosorbent assay) and PEVs (flow cytometry). Statistical analysis was performed using RM one-way analysis of variance with the Geisser–Greenhouse correction. Soluble P-selectin tended to increase at T30 compared with T0, while T90 levels returned to baseline values. Significantly higher circulating levels of PEVs CD61+/AnnV+ were observed at T30 and T90 compared to baseline confirming platelet hyperactivity. The detection and quantification of sP-sel and PEVs in equine racehorses during the training period appears to be a promising tool to study exercise-induced primary hemostatic changes and may provide an important marker for exercise selection.